ANALISIS BIBLIOMETRIK TAX AVOIDANCE DALAM SUDUT PANDANG EKONOMI DAN HUKUM - Budi Utami, Dela Wijayanti; Agus Santoso, Rachmat; Fitriana; Nurkhaeriyah, Nurkhaeriyah (Fakultas Hukum Universitas Muhammadiyah Cirebon, 2023)
Main Purpose - This study aims to present and explain tax avoidance by reviewing bibliometric analysis gathered from the Scopus database from 1955-2022. Method - The analysis method of this study uses a bibliometric analysis approach. Application system for data visualization uses VOSviewer and Microsoft Excel to perform data frequency analysis. Main finding : The result indicate that (1) Hanlon.m, ; Maydew E.L was the author who was most cited with 1589 quotes with a total of 3 articles and Sikka P was the author who produced the most articles, namely 5 articles with 519 citations. (2) The University of Oregon, United States is the institution that has produced the most articles about tax avoidance with 11 articles and 884 citations. (3) The United States is the largest country producing 229 articles with a total of 17,082 citations in 1955. Theory and practical Implication: Hopefully, this research helps encourage other researchers to conduct research on tax avoidance. Novelty: This study provides significant contributions and allows new insights about tax avoidance that has been growing enormously, nevertheless. Keywords: Bibliometric Analysis, Tax Avoidance, VOSviewer, Law